Pengaruh Stunting terhadap Kemampuan Pragmatik Anak pada Usia 4-6 Tahun di Kecamatan Jebres Kota Surakarta - Sevriano, Danendra Nadhif; Gunawan, Gunawan (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: The stunting’s problem is one of the problem that every government in this world is put their attention on it and that problem is also the main topic to discuss. That statement has corellation with the effort of Indonesian Government to stop stunting’s problem. Cognitive skills can also be impacted of stunting’s problem, the pragmatics skill is also the one of the cognitive skills that focused on the language aspect. WHO said that stunting has negative impact in the developmental language. Objectives: This research has goals to know the distribute of the impact of pragmatics skills of children that aged 4-6 years old in the Jebres Sub-District, Surakarta City. Methods: The research is a type of quantitative research that use cross sectional method. The purpose of using that method is to know the risk factor of other variable. Total sample that use in this research is 56 samples. The summary of data will be analyzed with bivariately and univariately analyzed. Result: The result of this research is use the Mann-whitney’s test to find the impact of one and other variable. The result is founded that the p-value = 0.000 (˂0.05), so the alternative hypothesis (Ha) is accepted. The stunting can be impacted the pragmatics skills of children aged 4-6 years old in Jebres Sub-District, Surakarta City. Conclusion: Based on the result of data analysis, we can make the conclusion that the stunting’s problem is impacted the pragmatics skill of children aged 4-6 tahun in the Jebres Sub-District, Surakarta City. Keywords : Stunting, Pragmatics Skill